Certolizumab pegol for the treatment of psoriasis. (4th March 2017) - Campanati, A.; Benfaremo, D.; Luchetti, M. M.; Ganzetti, G.; Gabrielli, A.; Offidani, A.
ABSTRACT: Introduction: Psoriasis is a chronic immunomediated and inflammatory disease involving mainly skin and joints, often associated with several metabolic and non-metabolic comorbidities. TNF-alpha inhibitors have shown long-term efficacy and safety/tolerability in psoriasis, and preliminary data support the use of certolizumab pegol (CZP) as well. Areas covered: The authors review the pharmacological properties of CZP, as well as its safety data and efficacy profile. They also review the quality of life outcomes related to CZP in psoriasis. The authors also provide their expert opinion on the subject. Expert opinion: CZP is a promising treatment for psoriasis owing to its rapid reduction of disease activity, long-term therapeutic efficacy – both in bio-naive and non-bio-naive patients, long term safety and low rate of site injection reactions. CZP seems to be a promising therapeutic option for psoriasis patients, although further evidence supporting the continuing clinical program for development of CZP in psoriasis is needed.